Analisis Kinerja Keuangan Dalam Mencapai Corporate Turnaround Pada Pt Fks Food Sejahtera Tbk Periode 2022-2024 - Juwita Dwi Hapsari; Melati Permaisuri; Cika Angelina (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2026)
This study aims to analyze the financial performance of PT FKS Food Sejahtera Tbk for the 2022–2024 period in an effort to achieve corporate turnaround. The research method applied is descriptive quantitative by dissecting the company's audited annual consolidated financial statements through three main parameters: liquidity ratio (Current Ratio), solvency ratio (Debt to Asset Ratio), and profitability ratio (Net Profit Margin). The results indicate a highly significant recovery trend following the critical phase. The company's liquidity improved drastically, with the CR leaping to 106.14% in 2024. Financial risk and reliance on external debt were successfully minimized, as evidenced by a consistent decline in the DAR value to below the 50% safety threshold (reaching 46.73%). Furthermore, the company's profitability successfully achieved an impressive turnaround, shifting from a negative net profit margin of -3.38% in 2022 to a positive 3.61% at the end of 2024. The success of this turning point indicates improvements in financial management that are capable of driving the recovery of company performance during the observation period.